2011
DOI: 10.1111/j.1740-8261.2011.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the Distal Phalanx and Associated Soft Tissue and Osseous Abnormalities in 22 Horses With Ossified Sclerotic Ungual Cartilages Diagnosed With Magnetic Resonance Imaging

Abstract: Ungual cartilage ossification in the forelimb is a common finding in horses. Subtle abnormalities associated with the ungual cartilages can be difficult to identify on radiographs. Magnetic resonance (MR) imaging findings of 22 horses (23 forelimbs) with a fracture of the distal phalanx and ossified ungual cartilage were characterized and graded. All horses had a forelimb fracture. Eleven involved a left forelimb (seven medial; four lateral), and 12 involved a right forelimb (five medial; seven lateral). All f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…Excellent agreement between radiographic and scintigraphic grades of ossification of the ungular cartilages has been previously identified, and all cartilages with a fracture had corresponding increased radiopharmaceutical uptake . Injuries to these structures are typically traumatic in origin and are associated with osseous remodeling . Increased deposition of radiopharmaceutical occurs at sites undergoing active modeling or remodeling, in association with osteoblastic activity .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Excellent agreement between radiographic and scintigraphic grades of ossification of the ungular cartilages has been previously identified, and all cartilages with a fracture had corresponding increased radiopharmaceutical uptake . Injuries to these structures are typically traumatic in origin and are associated with osseous remodeling . Increased deposition of radiopharmaceutical occurs at sites undergoing active modeling or remodeling, in association with osteoblastic activity .…”
Section: Discussionmentioning
confidence: 80%
“…11 Injuries to these structures are typically traumatic in origin and are associated with osseous remodeling. 2,8,9,12,15,16 Increased deposition of radiopharmaceutical occurs at sites undergoing active modeling or remodeling, in association with osteoblastic activity. 17 When ungular cartilages were analyzed alone, the agreement was stronger than when combined with chondral ligaments.…”
Section: Distal Phalanx and Ungular Cartilages And Chondral Ligamentsmentioning
confidence: 99%
“…PD, T2w and STIR images were consistent with inflammation/degenerative changes, while decreased signal on PD and T2w is consistent with fibrosis/scaring (Selberg andWerpy 2011). Maher et al (2011) have suggested that tendon lesions with increased signal on PD images without signal increase on STIR and T2w images can be associated with degeneration.…”
Section: Pathologymentioning
confidence: 76%
“…Hematoma, bone hemorrhage in most cases appears as increased signal on both T1-and T2w images (Selberg andWerpy 2011, Werpy 2012).…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation